Review Article: Skin Condition and Skin Care in Premature Infants - Yuri Widia; rosdiana, brigita ika (Faculty of Medicine, Universitas Airlangga, 2023)
Background: The majority of newborn skin care recommendations focus on concerns for healthy, full-term infants. Compared to mature infants, the skin of premature infants, those who are born at the gestational age of 37 weeks, is more vulnerable to injury, transepidermal water loss (TEWL), and transepidermal intoxication. There are no established guidelines for premature infant skin care. Discussion and review regarding this topic are needed. Purpose: To review the literature on skin conditions and skin care in premature infants. Review: The barrier function of premature skin is significantly compromised because the stratum corneum does not fully mature until late in the third trimester. Premature infants have immature skin with impaired barrier function characterized by high TEWL, increased absorption of chemicals, and increased risk of infection. Some particular issues in premature infant skin are controlling TEWL, avoiding mechanical damage, proper sterilization to control infection, awareness of percutaneous drug toxicity, appropriate bathing and umbilical cord care, and appropriate management of skin problems. Conclusion: Premature infant skin is more vulnerable due to immature development. Skin care for premature infants requires careful attention.